Kebebasan Berekspresi dan Ujaran Kebencian: Kajian Filsafat Hukum Terapan - Diah Imaningrum Susanti (SAPIENTIA ET VIRTUS, 2022)
To speak and to communicate is a form of freedom of expression protected as a human right. The main justifications for freedom of speech are philisophical, political, and individual reasons. Hate speech, is a name for speech intended to insult and stigmatized others based on race, gender, sexual orientation, or other forms of group membership. In Indoensia, hate speech symbolyzes the evolution of freedom of expression considering that so many hate speeches are carried out openly. This is facilitated by the presence of online media. With an Applied Legal Philosophy Approach, this paper examines John Stuart Mill’s thougts on freedom of expression as a manifestation of human rights, namely as a means to find the truth, and the limits of hate speech within the framework of human rights as well. The background of the emergence of the freedom of expression and the emergence of hate speech can be traced from developed countries such as Europe and America, where the context of regulating hate speech is that it prohibits racial discrimination. In Indonesia, this is not the main reason, so that the regulation of hate speechin various provisions is more about prohibitions so as not to interfere with religious values, morality, order, pubic interest, and the integrity of nation. This is further clarified by the publication of the Regulatory Norm Standar (Standar Norma Pengaturan/SNP) Number 5 concerning the Right to Freedom of Opinion and Expression stipulated by National Commission of Human Rights which is expected to be a guide for a number of important points in the lige of expression because it regulates speech and political, religious, artistic, symbolic expressions, rights on the protection of personal data, as well as freedom of the press, which does not eliminate the principles and character of Indonesia itself. Online intermediary platform that facilitates freedom of expression – incuding facilitates hate speech – need to be the object of state regulation as well as the speakers and recipients of the hate speech. Key words: freedom of expression; hate speech; applied legal philosohpy Abstrak Berujar dan berkomunikasi merupakan salah satu wujud kebebasan berekspresi yang dilindungi sebagai hak asasi manusia (HAM). Justifikasi kebebasan berbicara adalah alasan filosofis, politis, dan individual. Berujar yang bermuatan kebencian, dinamai dengan ujaran kebencian, merupakan julukan bagi ujaran yang ditujukan untuk menghina dan menstigmatisasi berdasarkan ras, gender, orientasi seksual, atau bentuk-bentuk lain keanggotaan kelompok. Di Indonesia, ujaran kebencian menyimbolkan evolusi kebebasan berpendapat mengingat begitu banyaknya ujaran yang mengandung kebencian dilakukan secara terbuka. Hal ini diperlancar dengan keberadaan media online. Dengan pendekatan Filsafat Hukum Terapan, tulisan ini mengkaji pemikiran John Stuart Mill tentang kebebasan berekspresi sebagai wujud dari HAM, yakni sebagai sarana untuk menemukan kebenaran, dan batas-batas ujaran kebencian dalam kerangka HAM juga. Latar belakang munculnya kebebasan berekspresi dan munculnya ujaran kebencian ditelusur dari negara-negara maju seperti Eropa dan Amerika, yang konteks pengaturan ujaran kebenciannya adalah bersifat larangan diskriminasi ras. Di Indonesia, hal ini bukan menjadi alasan utama, sehingga pengaturan ujaran kebencian dalam berbagai ketentuan lebih pada larangan-larangannya agar tidak mengganggu nilai-nilai agama, kesusilaan, ketertiban, kepentingan umum, dan keutuhan bangsa. Hal ini diperjelas lagi dengan diterbitkannya Standar Norma Pengaturan (SNP) Nomor 5 dari KOMNAS HAM tentang Hak atas Kebebasan Berpendapat dan Berekspresi, yang diharapkan menjadi pedoman bagi sejumlah poin penting dalam kehidupan berekspresi karena mengatur pidato dan ekspresi politik, ekspresi keagamaan, ekspresi seni, ekspresi simbolis, hak atas perlindungan data pribadi, serta kebebasan pers, yang tidak menghilangkan prinsip dan karakter Indonesia itu sendiri. Media intermediari online yang memfasilitasi kebebasan berekspresi, termasuk ujaran kebencian, perlu menjadi objek pengaturan negara juga selain peng-ujar dan penerima ujaran kebencian. Kata kunci : Kebebasan berekspresi; ujaran kebencian; filsafat hukum terapan.